STRATEGI DIFERENSIASI PRODUK DALAM MENGHADAPI PERSAINGAN KULINER (KASUS BISNIS SOP TUNJANG TAMPAN DI PEKANBARU) - Juang Novrianto; Lie Othman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study was conducted at the First Tunjang Sop located on Jl . Cinnamon Pekanbaru Riau , which is a company engaged in the trade . The purpose of this study was to determine the strategy of product differentiation in the face of the culinary competition in business tunjang perjama pekanbaru soup . The research methods include the location of the research conducted on the first attempt tunjang pekanbaru soup , types and sources of data used is primary data , where the data is obtained directly from the company include product differentiation strategy that made the first attempt tunjang pekanbaru culinary soup and secondary data is data annual obtained from the company's other sales data from the years 2008-2012 , and a general overview of the company , while the analysis of the data using the method of analyzing the data in this study would be conducted degan qualitative descriptive method .Based on the results of research on product differentiation strategy in the face of the culinary competition in the business case tunjang Handsome soup can be seen that most of the respondents to respond well enough that as many as 21 people , or 52.50 % , then the respondents who gave a good response ditangggapi many as 8 or 20 , 00 % and to respond less well addressed as many as 11 people or 27.50 %The obstacles in the face of the product differentiation strategy culinary competition among others : That the lack of parking, lack of ability of the company to maintain a corporate image , a lack of desire and willingness to further develop its business enterpriseFrom these results , the actual product being supported first Handsome culinary soup is considered to be able to compete , but business owners should still consider the quality of marketed products , as well as looking for new innovations . This is done so that businesses can compete soup first SOP tunjang To nex time .Key word : Product, differentiation, marketing strategy,business competition